Bankers in the Boardroom and Firm Performance in China. Issue 8 (2nd August 2016) - He, Qing; Rui, Oliver M.; Zhu, Chenqi
ABSTRACT: We use a dataset comprising the appointments of commercial bankers as board of directors at Chinese listed firms and find that financially distressed firms are more likely to recruit a commercial banker as a director of the board. The presence of a banker on the board increases access to bank loans, yet many investors react negatively to announcements of such appointments. We also find that such appointments are typically followed by a drop in the appointing firm's operating performance, and an increase in rent-seeking activities. This suggests that bank directors cannot strengthen corporate governance. Most financial resources are expropriated by corporate insiders.